Pengaruh Penerapan Model Pembelajaran Inkuiri Terbimbing Terhadap Motivasi dan Hasil Belajar Siswa pada Mata Pelajaran Biologi Kelas X SMA Negeri 3 Tana Toraja - Ruli, Fitha Febrilia; Hala, Yusminah; Syamsiah, Syamsiah (Universitas Negeri Makassar, 2018)
Abstract. This study is a quasy experimental with pretest posttest control group design that aimed to determine the influence of guided inquiry learning on students’ motivation and learning outcome. The population of this research was all of X grade students at SMA Negeri 3 Tana Toraja in academic year 2017/2018. Sampling technic used random sampling that choosed X MIA 3 grade as experiment group and X MIA 5 grade as control group. Technic of data collecting were test and non-test method which were analysed by using anacova. The results of this study showed that students’ motivation and learning outcome who taught by implementing guided inquiry learning in high category and there is significantly difference between students’ motivation and learning outcome who taught by implementing guided inquiry learning and direct instruction. Keywords: guided inquiry, learning motivation, learning outcome.